Study Of Clinker Grindability From YTL Cement, Kanthan, Perak - Syed Hussin, Azrina (Universiti Sains Malaysia, 2022)
The quality of the raw material, the chemical changes that occur throughout the burning and cooling processes, and the degree of grinding all affect the final clinker product's quality. Studies on clinker's mineralogy and chemistry will reveal details on the material's properties and the circumstances that prevail during different manufacturing stages. Research done into the factors that affect grindability during clinkering, including the primary phase (alite, belite, aluminate, and ferrite), degree of crystallisation, alite crystal size, and belite clusters. A high amount of alite and low content of belite and interstitial phases (aluminate and ferrite) are easier to grind rather than the clinker rich with belite and interstitial phases. Discover that the grinding of clinker depends on the chemical composition and mineralogical features. Grindability is further impacted by belite clusters and alite crystal cluster size. The grindability of the clinker reinforced again by running grindability index test which a grindability index test measures how well a material will hold up to being ground in a ball mill. The Grindability Index of various ores may be calculated and compared using this test. The harder it is to grind the material, the higher the grindability index.